The differential diagnosis and treatment of crossbites - Faber, R D (The Dental clinics of North America, 1981)
The purpose of this discussion was to give the practitioner a better understanding of the diagnostic processes involved in evaluating a crossbite and arriving at a differential diagnosis. It is hoped that the material presented helps to show the logical steps required to arrive at an intelligent diagnosis. The section on appliances was presented to show the range of treatment modalities available and to illustrate specific cases to show their effectiveness. It is important for the practitioner to realize that effective and efficient treatment of the patient must start with a clear diagnostic evaluation of the patient's problem.